CHINA'S AMBITION IN ENHANCING INDO-PACIFIC GEOPOLITICAL POWER THROUGH CHINA'S SPACE PROGRAM IN 2018-2024 - Nawa, Ahmad Sabiqun; Wibowo, Prihandono (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This study aims to analyze how China's space program is used as a strategic instrument in enhancing geopolitical power in the Indo-Pacific region in the 2018-2024 period. Using a qualitative approach and astropolitical theory, this study explores four main indicators: space technology mastery, space resource utilization, international cooperation, and space asset protection. The results show that China has achieved significant progress through the successful Chang'e exploration mission, the construction of the Tiangong space station, and the BeiDou navigation system that competes directly with the United States' GPS. In addition, China is actively forging space partnerships with developing countries and engaging in multilateral projects such as the International Lunar Research Station (ILRS). The exploration and utilization of resources such as helium-3 on the Moon marks a long-term strategic orientation in energy and technology. On the other hand, the strengthening of situational awareness systems in space and the potential for space defense demonstrate China's seriousness in safeguarding its strategic assets. In conclusion, China's space program not only reflects scientific progress, but is also a tool of diplomacy and power projection in the Indo-Pacific.